Destabilizing polymorphism in cervid prion protein hydrophobic core determines prion conformation and conversion efficiency - Hannaoui, Samia (PLoS Pathog, 2017)
Prion diseases are infectious neurodegenerative disorders of humans and animals caused by misfolded forms of the cellular prion protein PrP(C). Prions cause disease by converting PrP(C) into aggregation-prone PrP(Sc). Chronic wasting disease (CWD) is the most contagious prion disease with substantial lateral transmission, affecting free-ranging and farmed cervids. Although the PrP primary structure is highly conserved among cervids, the disease phenotype can be modulated by species-specific polymorphisms in the prion protein gene. How the resulting amino-acid substitutions impact PrP(C) and PrP(Sc) structure and propagation is poorly understood. We investigated the effects of the cervid 116A>G substitution, located in the most conserved PrP domain, on PrP(C) structure and conversion and on 116AG-prion conformation and infectivity. Molecular dynamics simulations revealed structural de-stabilization of 116G-PrP, which enhanced its in vitro conversion efficiency when used as recombinant PrP substrate in real-time quaking-induced conversion (RT-QuIC). We demonstrate that 116AG-prions are conformationally less stable, show lower activity as a seed in RT-QuIC and exhibit reduced infectivity in vitro and in vivo. Infectivity of 116AG-prions was significantly enhanced upon secondary passage in mice, yet conformational features were retained. These findings indicate that structurally de-stabilized PrP(C) is readily convertible by cervid prions of different genetic background and results in a prion conformation adaptable to cervid wild-type PrP. Conformation is an important criterion when assessing transmission barrier, and conformational variants can target a different host range. Therefore, a thorough analysis of CWD isolates and re-assessment of species-barriers is important in order to fully exclude a zoonotic potential of CWD.